2000
DOI: 10.1093/hmg/9.17.2531
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic effects of the melanocortin 1 receptor (MC1R) gene on human pigmentation

Abstract: Variants of the melanocortin 1 receptor (MC1R) gene are common in individuals with red hair and fair skin, but the relative contribution to these pigmentary traits in heterozygotes, homozygotes and compound heterozygotes for variants at this locus from the multiple alleles present in Caucasian populations is unclear. We have investigated 174 individuals from 11 large kindreds with a preponderance of red hair and an additional 99 unrelated redheads, for MC1R variants and have confirmed that red hair is usually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
213
3
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(228 citation statements)
references
References 27 publications
11
213
3
1
Order By: Relevance
“…They, therefore, suggested an altered expression of the wild type-allele by another mechanism. Flanagan et al, (2000) found that although the majority of the red-haired individuals are homozygous or compound heterozygous for MC1R variants, they found that individuals who were heterozygous had a different shade of red hair. Hence, the inheritance of the red hair and pale skin phenotype is not a simple autosomal recessive trait, as might be suggested by the results of compound heterozygosity and homozygosity of variants from the present and other studies.…”
Section: Resultsmentioning
confidence: 99%
“…They, therefore, suggested an altered expression of the wild type-allele by another mechanism. Flanagan et al, (2000) found that although the majority of the red-haired individuals are homozygous or compound heterozygous for MC1R variants, they found that individuals who were heterozygous had a different shade of red hair. Hence, the inheritance of the red hair and pale skin phenotype is not a simple autosomal recessive trait, as might be suggested by the results of compound heterozygosity and homozygosity of variants from the present and other studies.…”
Section: Resultsmentioning
confidence: 99%
“…It is highly polymorphic in human populations, and its allelic variation is the principle determinant of pigment phenotypes and skin phototypes in humans (Valverde et al 1995;Sturm 2002). Three common variants of MC1R (R151C, R160W, and D294H) have been associated with the so-called Red Hair Color (RHC) phenotype (Box et al 1997Smith et al 1998;Flanagan et al 2000;Palmer et al 2000;Bastiaens et al 2001a,b), characteristic of individuals with red hair, fair complexion, an inability to tan, and a tendency to freckle. Carrying a single RHC MC1R variant is associated with a significantly diminished ability of the epidermis to respond to damage by UV (Flanagan et al 2000;Box et al 2001;Healy et al 2001), presumably contributing to increased melanoma risk (Palmer et al 2000;Healy et al 2001).…”
Section: Msh Signalingmentioning
confidence: 99%
“…Three common variants of MC1R (R151C, R160W, and D294H) have been associated with the so-called Red Hair Color (RHC) phenotype (Box et al 1997Smith et al 1998;Flanagan et al 2000;Palmer et al 2000;Bastiaens et al 2001a,b), characteristic of individuals with red hair, fair complexion, an inability to tan, and a tendency to freckle. Carrying a single RHC MC1R variant is associated with a significantly diminished ability of the epidermis to respond to damage by UV (Flanagan et al 2000;Box et al 2001;Healy et al 2001), presumably contributing to increased melanoma risk (Palmer et al 2000;Healy et al 2001). However, the observation that RHC MC1R variants are associated with increased melanoma risk even in individuals with dark/olive complexions (Palmer et al 2000;Healy et al 2001;Kennedy et al 2001) suggests that MC1R have additional pigment-independent effect(s) on melanoma risk.…”
Section: Msh Signalingmentioning
confidence: 99%
“…Even a single variant allele results in skin that is at greater risk from UV. 4 By contrast, in Africans the gene is highly invariant, quite unlike most other genes in the African population, which usually show greater diversity than in Europe. This is clear evidence of selection to maintain function.…”
mentioning
confidence: 98%